ALPHABET OF CZECH REALITIES - Jovanov, Jane; Romashevska, Katerina (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
Since March 2016 a new project was initiated within the Faculty of Arts at Charles University in Prague. This project name is "Alphabet of Czech realities - electronic database of Czech realities in linguarealities in the Czech language". The timeframe for implementation of this project is 5 years with included research throughout the Czech Republics, all funded by the Ministry of Culture of the Czech Republic. This article provides an explanation of the main objective of the project and detail regarding the action plan and the target group. Keywords: realities, linguarealities, culture.